(untitled) (Journal of the Society for Musicology in Ireland, 2026)
A Review of John O’Flynn and Patricia Flynn (Eds.), Music Education for the Twenty-First Century: Legacies, Conversations, Aspirations, Studies in Irish Music Education, 1 (Cork: Cork University Press, 2023), ISBN: 9781782055792, 280pp, €49 (hardcover).